(untitled) (Journal of the College of Basic Education, 2022)
The study was conducted in the Insect Laboratory of the Faculty of Education at the Iraqi University during 2015 to study the effect of different concentrations of 1, 3 and 5 g of alcoholic extract raw powder of the fruits of black pepper Pipper nigrum per kg seeds on some aspects of the life of the beetle South cowpea Callosobruchus maculatus.Proven results of the study that the concentrations of different from the alcoholic extract raw powder of the fruits of black pepper caused a significant decrease in all aspects of life studied the insect of the first generation and the second compared to the treatment comparison although there is a direct correlation between the decline focus as the high concentration of 0.005g/kg was more influential in bringing about the decline. The results of the study outweigh the alcoholic extract the raw powder in the events influence decline as the number of eggs per female 131 in the first generation and 293 eggs / female and the number of adults emerging 33 and 272 seriously , and the percentage of the emergence of adult 31.4% and 92.8% and for 26.3 life cycle and 30.3 on the length of the age of 11 and 13.66 the day when the focus 0.005 extract and alcohol treatment comparison , and respectively. Results of the study have demonstrated the survival of the effectiveness of different treatments and their efficiency in influencing all life aspects in the second generation , and the percentage of loss in the seed weight , the study demonstrated an inverse relationship between the concentrations and the alcoholic extract raw powder and the percentage of loss in the first and second generation , but that there is a marked increase in the percentage of weight loss of seeds in the second generation , reaching 0.005 when the focus of the alcoholic extract of 3.9% in the first generation and 24.7 % in the second generation while the treatment in comparison with 55.4 and 72 % for the first and second generation , respectively. Results of the study demonstrated the presence of a significant statistical link between all facets of life studied the insect and the percentage of loss in seed weight in both generations